Smartphone application-based follow-up care of patients after bariatric surgery: A mixed-method study of usability - Cui Yang; Mia Kessler; Niki Taebi; Preetha Moorthy; Christoph Reissfelder; Mirko Otto; Georgi Vassilev (Digital Health, 2022)
Objective Due to potential short-term and long-term complications, adequate lifelong follow-up is crucial for patients after bariatric surgery. However, compliance with postoperative follow-up is poor despite clear national and international guidelines. This feasibility trial aimed to evaluate the usability of a smartphone application-based follow-up program in patients after bariatric surgery. Methods Patients were included after having undergone a primary bariatric surgery. Instead of attending meetings in our outpatient clinic, they were followed up using a smartphone application. After 6 months, the System Usability Scale (SUS) was used to measure participant perception. Additional interviews were performed to gain more insight into the usability of the app. Results Between August 2020 and February 2021, 52 patients met the inclusion criteria and agreed to participate in the study, of whom 5 (9.6%) dropped out of the study. At the time of analysis, 31 patients have been followed up for 6 months, among whom 26 patients completed the SUS questionnaire. The mean overall score of SUS is 82.1 ± 19.8. In the qualitative analysis, participants were generally positive about the follow-up care and found it easy to use, despite some minor technical problems. Conclusion Our smartphone app-based follow-up program was proven to be effective in the aftercare succeeding bariatric surgery. Our data indicates that the satisfaction, efficiency, learnability, and ease of use of the smartphone application were coherent in the acceptance and use of mobile technology by patients.